2010
DOI: 10.2166/wh.2010.136
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary Ames fluctuation assay assessment of the genotoxicity of drinking water that has been solar disinfected in polyethylene terephthalate (PET) bottles

Abstract: Though microbially safe, concerns have been raised about the genotoxic/mutagenic quality of solar-disinfected drinking water, which might be compromised as a result of photodegradation of polyethylene terephthalate (PET) bottles used as SODIS reactors. This study assessed genotoxic risk associated with the possible release of genotoxic compounds into water from PET bottles during SODIS, using the Ames fluctuation test. Negative genotoxicity results were obtained for water samples that had been in PET bottles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…They examined the efficiency of a range of SODIS bags configurations using E. coli in model and real surface water [8]. The release of potentially dangerous compounds from PET bottles into water under both solar disinfection and longterm exposure conditions has been studied by Ubomba-Jaswa et al For this purpose a biological approach was used in the form of the Salmonella Ames-Fluctuation assay to detect genotoxins in water samples stored in PET bottles exposed to SODIS conditions [81]. Under SODIS conditions, bottles were exposed to 6 h of sunlight, followed by overnight room temperature storage.…”
Section: Solar Reactors For Water Disinfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…They examined the efficiency of a range of SODIS bags configurations using E. coli in model and real surface water [8]. The release of potentially dangerous compounds from PET bottles into water under both solar disinfection and longterm exposure conditions has been studied by Ubomba-Jaswa et al For this purpose a biological approach was used in the form of the Salmonella Ames-Fluctuation assay to detect genotoxins in water samples stored in PET bottles exposed to SODIS conditions [81]. Under SODIS conditions, bottles were exposed to 6 h of sunlight, followed by overnight room temperature storage.…”
Section: Solar Reactors For Water Disinfectionmentioning
confidence: 99%
“…Even though researchers have, so far, failed to detect PET plastic photodegradation products or any other harmful or genotoxic substances at concentrations likely to be harmful in solar disinfected water [78,81], concerns about such contaminants remain a significant barrier to increased uptake of SODIS. This psychological barrier must be addressed if SODIS usage is to be increased.…”
Section: Solar Reactors For Water Disinfectionmentioning
confidence: 99%
“…Process efficiency depends on a range of environmental parameters including solar irradiance (which, in turn, depends on latitude, time of day, and atmospheric conditions), organic loading turbidity of the water, and the load and nature of the microbial contamination, which affects the time required to reach a certain disinfection level as different microorganisms have different sensitivities to solar disinfection. There are also some questions about the safety of using plastic bottles exposed to sunlight for prolonged times regarding potential leaching of chemical derivates [11]. Furthermore, SODIS is user dependent in terms of the treatment time and there is no quality assurance for the process.…”
Section: Simple Solar Technologies For Low-income Communitiesmentioning
confidence: 99%
“…Treatment methods recommended in the region included boiling and the use of chlorine tablets. However, households considered these methods too expensive to use, a finding also reported by Baguma et al [38] who carried out a study in the Luwero District, north of the Ugandan capital Previous studies have examined risks associated with the photodegradation of the plastic container material after prolonged use [39,44]. These studies reported no genotoxic risks associated with SODIS bottle use over periods of up to 6 months.…”
Section: Discussionmentioning
confidence: 89%